The Effect of a Mindfulness-based Cognitive Stimulation Program on Cognitive Function, Depression, and Psychological Well-being of Women in Destitute Protection Centers with Mild Cognitive Impairment - Wiriyatuntikul, Piyanuch; Kaesornsamut, Phuangphet; Pianchob, Sudarat (Nursing Science Journal of Thailand, 2023)
Purpose: This research aimed to examine the effectiveness of a mindfulness-based cognitive stimulation program on cognitive function, depression, and psychological well-being of women, aged over 50 years with mild cognitive impairment. Design: Quasi-experimental research with two groups of repeated measures design were studied: pre-experimental, post-experimental, and a four-week follow-up. Methods: Convenience sampling was used to recruit 56 women who met the inclusion criteria from two Destitute Protection Centers, with 28 women in each center. The women in intervention group participating in mindfulness-based cognitive stimulation program attended 8 two-hour sessions during 4 weeks. The control group received only routine care. The data were analyzed using descriptive statistics, independence t-test, and One-Way Repeated Measures ANOVA. Main finding: The results showed that subjects in the intervention group, compared to those in the control group, had significantly increased cognitive function and psychological well-being as well as decreased depressive symptoms. Moreover, subjects in the intervention group had a significantly increased cognitive function and psychological well-being as well as decreased depressive symptoms at immediately after the intervention and 4 weeks after the intervention, comparing to those at baseline. Conclusion and recommendations: The findings document the effectiveness of the mindfulness-based cognitive stimulation program on enhancing cognitive function and psychological well-being as well as diminishing depressive symptoms in women with mild cognitive impairment. Therefore, implementing this intervention program at persons with mild cognitive impairment is recommended in order to promote cognitive function and psychological well-being as well as prevent depression.